FACTORS AFFECTING ACADEMIC STAFFS’ UNIVERSITY SATISFACTION: COMPARISON BETWEEN VOCATIONAL SCHOOLS AND SCHOOLS/FACULTIES - Hüseyin Dalğar; Ali Murat Alparslan; Onur Sungur (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Consideringthat the number of universities has increased considerably in the last 10years, attracting qualified university students and academicians and keepingthem has become very important. Taking into account that that there are manyalternatives for academicians, it is necessary to be sensitive to theirsatisfaction with the university. It is also believed that the satisfaction ofacademicians reflects on students’ satisfaction. The findings of the researchon the satisfaction levels of academicians can be a guide for the short andlong term plans of the strategic plans of universities.Inthis context, the purpose of this study is to investigate the determinants ofsatisfaction of academicians from their university and to reveal their relativeeffects. It is assumed that these determinants may differ in the context ofVocational School and School/Faculty. As a result of the field research whichwas carried out on 326 academicians in Mehmet Akif Ersoy University, positiverelations with the top management, positive relations with the unit manager,attitude of the management to the academic study incentives, administrativefunctioning, physical-technical infrastructure and socio-culturalinfrastructure satisfaction were determined as the precursors of universitysatisfaction. In addition, the impact levels of the aforementioned elements onoverall satisfaction have been presented in terms of Vocational Schools andSchools/Faculties